Identification of the bioactive compounds of skin mucus from asian swamp eel (monopterus albus) using liquid chromatography quadrupole-time-of-flight mass spectrometry - Hilles, Ayah Rebhi; Mahmood, Syed; Kaderi, Mohd Arifin; Hashim, Ridzwan (Malaysian Society for Biochemistry and Molecular Biology, 2019)
Asian swamp eels have been widely accepted as sources of food, especially among various Asian cultures. However, their potential values as novel sources of therapeutic agents have not been widely appreciated. Like most other tropical fishes and amphibians, the outer integumentary system of Monopterus albus is covered with mucus layers, which may act as a mechanical and biochemical barrier for their skin. The biochemical components of these mucus layers may have certain compounds that may be medically beneficial to human. The current study was interested to screen the bioactive compounds of skin mucus from the tropical Asian swamp eel (Monopterus albus) using Liquid Chromatography Quadrupole-Time-Of-Flight Mass Spectrometry (LC-QTOF-MS), for this purpose, eel skin mucus extract was used for LC-QTOF-MS analysis. The screening results for the bioactive compounds revealed different bioactive compounds which possess multiple biological properties mainly anticancer, antimicrobial, anti-inflammatory and antioxidant activities. In conclusion, the current study illustrated that eel skin mucus contain different bioactive compounds which might be consider as therapeutic-promising agents.